PEMANFAATAN PUPUK ORGANIK CAIR UNTUK MENINGKATKAN HASIL TANAMAN CABAI - Idaryani Idaryani; Warda Warda (Biology Department, Mathematics and natural science, Tadulako University, 2018)
Attempt that applicable to improve the fertility of the soil is by the granting of a mixture of cow urine and fertilizing macro nutrient elements N, P, K that required by plants in large amounts. Fertilizers containing nutrient elements N, P, K used was Urea, SP-36 and the KCl will increase the availability of nutrient elements N, P, K into the soil so the nutrient elements for plants can be fulfilled. Use of suitable fertilizer highly effective for plant growth and development. The purpose of this study is to get a right dose of liquid organic fertilizers (LOF) biourine with combination of organic fertilizer on the chili plant outputs of the study is a combination of fertilization doses of liquid organic fertilizer (LOF) biourine with the precise inorganic fertilizers on chili plants. The study was carried out in the Deceng village, Pattiro Camba District, Maros, in August-November 2015. The study was arranged in Factorial Block Randomized Design with two factors, where the factor I is anoragnik fertilizer doses (4 levels) i.e. P1 = based on recommendations; P2 = 125% of recommendations; P3 = 50% of recommendations; and P4 = fertilization based on how farmers. Factor II is the concentration biourine (four level) consists of B0 = without biourine; B1 = 10 ml 1 liter water-1; B2 = 20 ml 1 liter water-1; B3 = 30 ml 1 liter water-1, and repeated three times. Total plot was 48. The parameters observed were higher plants (30.60, and 90 DAP), number of branches, stem diameter, age of flowering, the number of pieces per plant, fruit weight and yield of fresh fruit. The use of inorganic fertilizers provide an obvious influence against almost all the parameters except the flowering age. The granting of biourine fertilizers provide an obvious influence on all the parameters are observed, whereas the second interaction treatment does not provide any real influence on almost all treatment except on the weight of the fruit per plant. From the results it can be concluded that the use of liquid organic fertilizer biourine the real effect to increased production of chili plants.